Water mass gradients of the mid-depth Southwest Atlantic during the past 25,000 years - Pöppelmeier, Frerk; Blaser, Patrick; Süfke, Finn; Lippold, Jörg (Earth and planetary science letters, 2020)
Antarctic Intermediate Water (AAIW) plays a central role in the Atlantic Meridional Overturning Circulation (AMOC) as the return flow of Northern Sourced Water (NSW) and is therefore of significant importance for the global climate. Past variations of the boundary between AAIW and NSW have been extensively investigated, yet available results documenting the prevailing depth of this boundary and the southern extent of NSW during the last ice age remain ambiguous. Here, we present five new timeseries focusing on the authigenic neodymium isotope signal in sediment cores retrieved from the Southwest Atlantic covering the past 25,000 years. The sites are situated along the southern Brazil Margin and form a bathymetric transect ranging between 1000 and 3000 m water depth, encompassing the modern water mass boundaries of AAIW and NSW and therefore allow their reconstruction since the Last Glacial Maximum (LGM). The new Nd isotope records show little change between the LGM and early deglaciation as well as relatively homogeneous values over the full depth range of the cores during these times. These results strongly contrast with epibenthic foraminiferal stable carbon isotope records (δ13C) from the same sites which exhibit highest glacial values at mid-depths, presumably related to NSW mixing into southern sourced water. We propose that the discrepancy between these two independent water mass proxies is partly related to changes in Nd end member properties of glacial AAIW. The combination of elevated glacial dust fluxes and, as a result, sustained export productivity caused high sinking particle flux in the western South Atlantic, where AAIW is forming. Higher particle flux would have increased the removal (scavenging) of Nd from shallow waters thus reducing the Nd concentration and overprinting the isotopic signature of the glacial AAIW end member. Only under consideration of changes in Nd end member properties along with non-conservative processes such as remineralization of organic matter influencing past seawater δ13C can we reconcile the water mass reconstructions from both proxies.